Herpetofauna of Stara Zagora, Southern Bulgaria: Species composition and distribution along the natural habitat-urban areas gradient - Dian Georgiev; Dilian Georgiev (Trakia Journal of Sciences)
Herpetofauna of Stara Zagora city is characterized by exceptional species richness. In the this urban area and its adjacent territories, twenty-nine species from 13 families and four orders of class Amphibia and class Reptilia were found. From all species encountered in the studied region, 21 were established in suburban zones. Ten species were registered in residential areas and their adjacent territories, and 18 species – in city parks. An obvious increase in number of species and their spread to the peripheral and central city areas was observed. The least number of species (5 sp.) was observed in construction areas, areas of intensive crop farming (6 sp.) and around administrative buildings (6 sp.).